(untitled) (Tanzania Medical Journal, 2024)
Background Tanzania is among the five countries with the highest estimated number of newborns with Sickle cell disease (SCD) in sub-Saharan Africa. Hydroxyurea (HU) is recommended for infants from 9 months of age, all children and adolescents with Sickle Cell Anaemia (SCA) however it’s utilization in clinical practice is not optimal. Materials and Methods A mixed method study was conducted from October 2019 to January 2020 among children with SCA attending a tertiary paediatric haematology clinic at Muhimbili National Hospital. Children between the age of 6 months and 18 years were consecutively included based on inclusion/exclusion criteria set for the quantitative study. Structured questionnaires were used to collect data based on the purpose of the study. Caregivers of children with SCA, clinicians, and pharmacists participated in four focus group discussions to explore barriers and facilitators to hydroxyurea (HU) use. A sequential explanatory design was used, quantitative data analysis was conducted using SPSS (version 21) and content thematic approach for the qualitative data. Results Out of 400 children enrolled, 59% were males with a median age of diagnosis at 2 years and 8 months (IQR 1- 4). The coverage gap to initiation of HU was 65% (260/400) and children who were on HU being less likely to be transfused (6.4% Vs 14.6%, p value < 0.05), and had a trend of lesser hospitalization, (9.3% Vs 12.3%, p value 0.33) compared to non-users respectively. Common reasons holding the coverage were caregiver’s unawareness (61%) and lack of medical insurance/affordability (29%). Qualitative learnings showed facilitators for HU use included improved symptoms, good compliance, and financial stability/active medical insurance. Even with medical insurance, longer time to get special permit to access it and fare/monthly clinic attendance because of limited supply were among the barrier to use HU. Poor knowledge/awareness for both parents and clinicians, and fear of side effects were also reported. Conclusion and recommendations Children with SCA were diagnosed late, and coverage for HU use was low. Increasing awareness, effective use of medical insurance and improving access of hydroxyurea within the health system would be vital for quality care among children with SCA.